A genetic variant in the promoter of lncRNA MALAT1 is related to susceptibility of ischemic stroke - Wang, Yan (Lipids Health Dis, 2020)
BACKGROUND: Metastasis-associated lung adenocarcinoma transcript-1 (MALAT1) was aberrantly expressed in diverse diseases. Particularly in ischemic stroke (IS), the abnormal expression of MALAT1 played important roles including promotion of angiogenesis, inhibition of apoptosis and inflammation and regulation of autophagy. However, the effects of genetic variation (single nucleotide polymorphisms, SNPs) of MALAT1 on IS have rarely been explored. This study aimed to investigate whether SNPs in promoter of MALAT1 were associated with the susceptibility to IS. METHODS: A total of 316 IS patients and 320 age-, gender-, and ethnicity-matched controls were enrolled in this study. Four polymorphisms in the promoter of MALAT1 (i.e., rs600231, rs1194338, rs4102217, and rs591291) were genotyped by using a custom-by-design 48-Plex SNPscan kit. RESULTS: The rs1194338 C > A variant in the promoter of MALAT1 was associated with the risk of IS (AC vs. CC: adjusted OR = 0.623, 95% CI, 0.417–0.932, P = 0.021; AA vs. CC: adjusted OR = 0.474, 95% CI, 0.226–0.991, P = 0.047; Dominant model: adjusted OR = 0.596, 95% CI, 0.406–0.874, P = 0.008; A vs. C adjusted OR = 0.658, 95% CI, 0.487–0.890, P = 0.007). The haplotype analysis showed that rs600231-rs1194338-rs4102217-rs591291 (A-C-G-C) had a 1.3-fold increased risk of IS (95% CI, 1.029–1.644, P = 0.027). Logistic regression analysis identified some independent impact factors for IS including rs1194338 AC/AA, TC, TG, HDL-C, LDL-C, Apo-A1, Apo-B and NEFA (P < 0.05). CONCLUSIONS: These results suggest that the rs1194338 AC/AA genotypes may be a protective factor for IS.